2020
DOI: 10.2514/1.j058254
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Mode Analysis on H2–Air Rotating Detonation Waves in a Hollow Combustor

Abstract: to initiate your request. See also AIAA Rights and Permissions www.aiaa.org/randp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A hot jet with p = 2 MPa, T = 2500 K, and u = 800 m/s was used to initiate the detonation waves. This RDC initiation method is different from the previous work 7,25 on RDW multiplicity, in which the multiple detonation waves are artificially ignited by several hot spots. Here, only a single wave is ignited and the additional detonative waves form spontaneously, as shown in detail below.…”
Section: Two-dimensional (2d) Rdc Configuration and Initial And Bound...mentioning
confidence: 79%
See 1 more Smart Citation
“…A hot jet with p = 2 MPa, T = 2500 K, and u = 800 m/s was used to initiate the detonation waves. This RDC initiation method is different from the previous work 7,25 on RDW multiplicity, in which the multiple detonation waves are artificially ignited by several hot spots. Here, only a single wave is ignited and the additional detonative waves form spontaneously, as shown in detail below.…”
Section: Two-dimensional (2d) Rdc Configuration and Initial And Bound...mentioning
confidence: 79%
“…6 In the past decade, significant progress was achieved in understanding the operating mechanism RDCs. For example, the initiation characteristics, [7][8][9] detailed flow field structures, [10][11][12][13][14] various instabilities of the rotating detonation waves (RDWs), 7,[15][16][17][18] interaction between the RDWs and injection plenum, 6,[19][20][21] and propagation modes of the RDWs 16,19,[22][23][24][25] have been widely studied. When implemented as a power device, a RDC must operate stably in the desired operational mode.…”
Section: Introductionmentioning
confidence: 99%
“…And instead of the annular combustion chamber, it is easier to establish an H 2 /air rotating detonation in the hollow combustion chamber. Lin et al (2015) and Lin et al (2020) experimentally validated that utilizing the pre-detonator and increasing mass flow rate play an important role in the stability of detonation propagation. The result indicated that injecting enough CH 4 /O 2 mixture is the essential condition for sustaining a stable CRDW.…”
Section: Introductionmentioning
confidence: 91%
“…In response to some of the most recent research progress, we have compiled this Special Section on "Recent Progress on Rotating Detonation and Its Application," comprising one survey [15] and seven regular technical articles [16][17][18][19][20][21][22]. The survey [15] provides a comprehensive introduction to recent progress and development trends of the continuous detonation engine, particularly within the last five years.…”
mentioning
confidence: 99%
“…They show that the outflow direction can be controlled with guide vanes mounted ahead of the combustor. Lin et al [18] experimentally study RDWs and their propagation modes in a hollow combustor with hydrogen and air. Prakash et al [19] numerically replicate the flow phenomena observed in Burr and Yu's experiments [23].…”
mentioning
confidence: 99%